2011
DOI: 10.1007/bf03391773
|View full text |Cite
|
Sign up to set email alerts
|

Self-Monitoring During Spelling Practice: Effects on Spelling Accuracy and On-Task Behavior of Three Students Diagnosed With Attention Deficit Hyperactivity Disorder

Abstract: We used a multiple baseline across subjects design to investigate the effects of self-monitoring on the on-task behavior and spelling accuracy of three fifth-grade students diagnosed with attention deficit hyperactivity disorder (ADHD) during an independent spelling practice period in the general education environment. We also compared their on-task levels to that of peers without disabilities in the same classroom context before and after the self-monitoring intervention. Our results showed that time on-task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Positive indirect effects on behavioral outcomes of classmates were found for two out of three studies. An effect size of 1.46 was obtained for a study implementing a self-regulation intervention [ 53 ]. Two other studies applying a combined [ 54 ] and a self-regulation intervention [ 55 ] used data of different classmates and showed a behavioral improvement (34% decrease in off-task behavior) and deterioration (2% decrease in on-task behavior) respectively during intervention phases compared to baseline phases.…”
Section: Resultsmentioning
confidence: 99%
“…Positive indirect effects on behavioral outcomes of classmates were found for two out of three studies. An effect size of 1.46 was obtained for a study implementing a self-regulation intervention [ 53 ]. Two other studies applying a combined [ 54 ] and a self-regulation intervention [ 55 ] used data of different classmates and showed a behavioral improvement (34% decrease in off-task behavior) and deterioration (2% decrease in on-task behavior) respectively during intervention phases compared to baseline phases.…”
Section: Resultsmentioning
confidence: 99%
“…First, the results provide additional empirical support for the effectiveness of a vibrating electronic device to tactilely cue students to self-monitor. Several studies have demonstrated the effectiveness of this technique in prompting students to self-monitor on-and off-task behavior while completing academic tasks such as math and spelling (e.g., Farrell & McDougall, 2008;Legge, DeBar, & Alber-Morgan, 2010;Rafferty, Arroyo, Ginnane, & Wilczynski, 2011). However, few studies have investigated the use of tactile cues within a self-monitoring intervention targeting onand off-task behavior during homework.…”
Section: Discussionmentioning
confidence: 99%
“…CECs Standards for Evidence-Based Practices (2014) that consisted of 22 component items across eight quality indicators (QIs) for SCRDs were used to determine methodological quality of reviewed studies. None of the 20 studies met all 22 items, although eight met 21 (Bedesm, 2012;Creel et al, 2006;Gureasko-Moore et al, 2007;Rafferty, 2012;Rafferty et al, 2011;Rock, 2005;Rock & Thread, 2007;Wills & Mason, 2014). The lowest score (16) was obtained for Coughlin et al (2012).…”
Section: Methodological Quality Indicatorsmentioning
confidence: 99%
“…Some studies had only one dependent variable such as following directions (Agran et al, 2005) to such multi-component variables as those that make up SLANT behaviors: sit up, look at the person talking, activating thinking, noting key information, and tracking the talker (Amato-Zech et al, 2006). Curiously, one study targeted engaging in the self-monitoring process (i.e., looking at the self-monitoring card, tallying self-monitoring card) in addition to looking at a spelling list and hand raising (Rafferty, Arroyo, Ginnane, & Wilczynski, 2011). There were also a number or dependent variables that lacked any specific target behavior such as "engaged in behaviors specified by the teacher," "percentage of classroom preparation skills as determined by the teacher"…”
Section: Descriptive Features Of Included Studiesmentioning
confidence: 99%